2017
DOI: 10.1038/s41598-017-02037-z
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin II type 1/adenosine A 2A receptor oligomers: a novel target for tardive dyskinesia

Abstract: Tardive dyskinesia (TD) is a serious motor side effect that may appear after long-term treatment with neuroleptics and mostly mediated by dopamine D2 receptors (D2Rs). Striatal D2R functioning may be finely regulated by either adenosine A2A receptor (A2AR) or angiotensin receptor type 1 (AT1R) through putative receptor heteromers. Here, we examined whether A2AR and AT1R may oligomerize in the striatum to synergistically modulate dopaminergic transmission. First, by using bioluminescence resonance energy transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 81 publications
(96 reference statements)
0
5
0
Order By: Relevance
“…In addition, our D 2 R homodimer model with a TM5–TM6–TM5–TM6 interface, in accordance with a previously published D 2 R–mGlu5 heterodimer model presented by Qian et al (2018) [40], is physically stable over microsecond-length MD simulations. In addition to this homodimeric interface, it has been widely described that D 2 R heteromerizes through a TM4–TM5–TM4–TM5 interface with other class A GPCRs, such as A 2a and AT1 receptors [35,36,37,38,39]. Therefore, our results raise questions about the oligomerization interfaces D 2 R may form.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In addition, our D 2 R homodimer model with a TM5–TM6–TM5–TM6 interface, in accordance with a previously published D 2 R–mGlu5 heterodimer model presented by Qian et al (2018) [40], is physically stable over microsecond-length MD simulations. In addition to this homodimeric interface, it has been widely described that D 2 R heteromerizes through a TM4–TM5–TM4–TM5 interface with other class A GPCRs, such as A 2a and AT1 receptors [35,36,37,38,39]. Therefore, our results raise questions about the oligomerization interfaces D 2 R may form.…”
Section: Discussionmentioning
confidence: 62%
“…On the other hand, successive deletion of TM domains of the D 2 R and cysteine cross-linking studies revealed that the most critical areas involved in the intermolecular hydrophobic interactions for dimerization resided in TM4 [33,34]. In addition, the TM4–TM5–TM4–TM5 and TM5–TM6–TM5–TM6 interfaces have been widely described to be involved in D 2 R hetero-oligomerization with other class A GPCRs [35,36,37,38,39,40]. In 2014, Guitart et al [41] reported that dopamine D 1 receptor (D 1 R) TM5- or TM6-derived single peptides were able to reduce D 1 R homodimerization.…”
Section: Introductionmentioning
confidence: 99%
“…MODELLER V9.21 was used to rebuild the missing residues in ICL3 of δOR (residue number: 245–250), H8 of μOR (residue number: 346–352), and H8 of δOR (residue number: 329–335), as done in many computational works of GPCRs. Following a general construction way of GPCR dimers in the absence of corresponding crystal structures, ,, the two monomers (μOR and δOR) were aligned onto the μOR homodimer crystal structure (PDB ID: 5C1M) with the TM1-TM2-H8/TM1-TM2-H8 interface, which was taken as the input of ROSETTA to further refine its configuration. Similar to docking operations of Rosetta in some MD works, , default values of some key parameters, for example, a perturbation of 3 Å between proteins, 8° of tilt and 360° rotation around protein centers, were used to generate 1000 solutions. The best docked heterodimer was identified in terms of the ROSETTA interface score (I_sc) and acceptable membrane-compatibility, which was used to conduct subsequent MD simulation.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, in the striatum, the combined use of two receptor antagonists inhibited the effects produced by the heterodimerization of adenosine A2A receptor (A2AR) and AT1R. These findings can be helpful for the treatment of tardive dyskinesia (TD) [ 91 ]. However, AT1R antagonist losartan enhanced the interaction between AT1R and dopamine D1 receptor (D1R).…”
Section: Non-classical Allostery Of At1rmentioning
confidence: 99%